Complete mitochondrial DNA sequence of a Conoidean gastropod, Lophiotoma ( Xenuroturris) cerithiformis: Gene order and gastropod phylogeny - Bandyopadhyay, Pradip K.; Stevenson, Bradford J.; Cady, Matthew T.; Olivera, Baldomero M.; Wolstenholme, David R. (Toxicon (Oxford), 2006)
We have determined the first complete nucleotide sequence of the mitochondrial genome of a venomous mollusc, the Conoidean gastropod, Lophiotoma ( Xenuroturris) cerithiformis. It is 15,380 nucleotide pairs (ntp) and encodes 13 proteins, two ribosomal RNAs and 22 tRNAs of the mitochondrion's own protein synthesizing system. The protein mRNAs, ribosomal RNAs and 13 of the tRNAs are transcribed from the same strand, the remaining tRNAs from the other strand. The longest segment of unassigned sequence is 139 ntp and includes a 82 ntp segment that is a perfect inverted repeat sequence of 37 ntp separated by 8 nt. The gene arrangement of L. cerithiformis mtDNA shows remarkable similarity to the gene arrangements of mtDNAs of the vetigastropod Haliotis rubra, the polyplacophoran Katharina tunicata and the cephalopod Octopus vulgaris, but differs dramatically from the gene arrangements found in the mtDNAs of pulmonate and opisthobranch gastropods, as well as mtDNAs of bivalves and scaphopods. A single sixteen gene inversion that distinguishes L. cerithiformis mtDNA from mtDNAs of H. rubra, K. tunicata and O. vulgaris is shared by mtDNA of a littorinomorph gastropod Littorina saxitalis, suggesting a close relationship of conoidean and littorinomorph gastropods.